2020
DOI: 10.1101/2020.04.06.20054825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypertension in patients hospitalized with COVID-19 in Wuhan, China: A single-center retrospective observational study

Abstract: Objectives: It is unclear whether patients with hypertension are more likely to be infected with SARS-COV-2 than the general population and whether there is a difference in the severity of COVID-19 pneumonia in patients who have taken ACEI/ARB drugs to lower blood pressure compared to those who have not. Methods: This observational study included data from all patients with clinically confirmed COVID-19 who were admitted to the Hankou Hospital, Wuhan, China between January 5 and March 8, 2020. Data were extrac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 20 publications
0
72
0
1
Order By: Relevance
“…All of the selected studies were published in 2020 and were all of observational nature 17‐34 . In seven studies, the outcome that matched our research question was death 17,20,21,26‐28,31 ; in two studies, severe pneumonia 23,34 ; in three studies, critical or severe pneumonia 18,19,32 ; in one study, death or critical or severe pneumonia 33 ; in one study, severe pneumonia or death 24 ; and in one study, death, admission to ICU or mechanical ventilation requirement 25 .…”
Section: Resultsmentioning
confidence: 96%
“…All of the selected studies were published in 2020 and were all of observational nature 17‐34 . In seven studies, the outcome that matched our research question was death 17,20,21,26‐28,31 ; in two studies, severe pneumonia 23,34 ; in three studies, critical or severe pneumonia 18,19,32 ; in one study, death or critical or severe pneumonia 33 ; in one study, severe pneumonia or death 24 ; and in one study, death, admission to ICU or mechanical ventilation requirement 25 .…”
Section: Resultsmentioning
confidence: 96%
“…Further, abstracts of 98 articles were read and subsequently, the full text of 41 articles were reviewed. Of these, sixteen articles were shortlisted which compared the clinical and/or mortality outcomes of COVID-19 patients on ACEI or ARB with non-users [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Finally, these sixteen studies were included for review and out of these, nine and five studies were included in the meta-analysis of mortality and severity outcomes in COVID-19 patients on ACEI/ARB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…et al found a slightly lower rate of severe outcomes which included admission to the intensive care unit, the use of noninvasive or invasive mechanical ventilation, or death in patients on ACEI/ARB (24.8%) versus no ACEI/ARB (24.9%). [12,13,15,16,19,20,[23][24][25][26][27]. (Table 2) On the contrary, Guo [13,23].…”
Section: Resultsmentioning
confidence: 99%
“…After screening 343 citations, 13 observational studies were included (Figure 1) [18][19][20][21][22][23][24][25][26][27][28][29][30], combining to a total sample of 14,364 participants. The characteristics of included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%